(untitled) (VITAE Academia Biomédica Digital, 2025)
Background: Diabetes has been found to be one of the leading comorbidities associated with fatality in COVID-19 patients. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) entry is facilitated by interaction with Angiotensin Converting Enzyme-2 (ACE2) and possible polymorphisms in ACE2 can be a determining factor in host-viral protein interaction. A significant shift of healthcare towards "Telemedicine" is also on the rise. In this review, the possible effects of ACE2 polymorphisms on SARS-CoV-2 entry along with the escalation of "telemedicine" is discussed. Method: An expansive literature search using keywords: "COVID-19", "SARS-CoV-2", "diabetes", "type 2 diabetes", "type 1 diabetes", "ACE2", "polymorphism", "DPP4" and "telemedicine" was conducted on Pubmed and EMBASE till 7th August 2020. Result: Possible polymorphisms in ACE2 gene can play a role in influencing the virus entry in host body. Telemedicine can bring a new revolution for medical sector. Conclusion: COVID-19 severity is more heinous among diabetic population. So far, the in-silico studies involving human ACE2-viral Spike (S) interaction showed inconsistent predictions regarding some SNPs. But without actual in-vivo studies, a holistic understanding can’t be established. © 2020 Primary Care Diabetes Europe. Published by Elsevier Ltd. All rights reserved.